Acremocholone, an Anti‐Vibrio Steroid from the Marine Mesophotic Zone Ciocalypta Sponge‐Associated Fungus Acremonium sp. NBUF150. Issue 4 (9th March 2022) - Feng, Yun‐Ping; Wang, Hong‐Kun; Wu, Jia‐Ling; Shao, Peng; Zhou, Wen‐Li; Lai, Qi‐Liang; Lin, Hou‐Wen; Naman, C. Benjamin; Wang, Ting‐Ting; He, Shan
Abstract: Mesophotic coral ecosystems (MCEs) represent an underexplored source of intriguing natural products. Efforts to discover bioactive metabolites from sponge‐associated fungi in MCEs identified a new steroid, acremocholone (1 ) and its three known analogs (2 –4 ), from Acremonium sp. NBUF150. The Acremonium sp. NBUF150 was isolated from a Ciocalypta sponge located 70 m deep within the South China Sea. The planar structures and absolute configuration of 1 –4 were determined from NMR‐derived spectroscopic data, HR‐ESI‐MS, and X‐ray crystallography. Compound 1 exhibited antimicrobial inhibition against Vibrio scophthalmi, V. shilonii and V. brasiliensis at minimum inhibitory concentrations of 8 μg/mL; compound 2 inhibited V. shilonii and V. brasiliensis at 8 and 32 μ g /mL, respectively, and compound 4 inhibited growth of V. brasiliensis at 16 μg/mL. Sponge associated fungi from MCEs represent a promising resource of anti‐ Vibrio drug leads for aquaculture use. Abstract :